Spatio-Temporal Variability of Peat CH4 and N2O Fluxes and Their Contribution to Peat GHG Budgets in Indonesian Forests and Oil Palm Plantations - Swails, Erin; Hergoualc’h, Kristell; Verchot, Louis; Novita, Nisa; Lawrence, Deborah (Frontiers in Environmental Science, 2021)
Land-use change in tropical peatlands substantially impacts peat emissions of methane (CH4) and nitrous oxide (N2O) in addition to emissions of carbon dioxide (CO2). However, assessments of full peat greenhouse gas (GHG) budgets are scarce and CH4 and N2O contributions remain highly uncertain. Over a period of one and a half year, we monitored monthly CH4 and N2O fluxes together with environmental variables in three undrained peat swamp forests and three oil palm plantations on peat in Central Kalimantan and evaluated drivers of variation in trace gas fluxes. We computed peat net GHG budgets in both ecosystems using soil respiration and litterfall rates measured concurrently with CH4 and N2O fluxes, site-specific soil respiration partitioning ratios, and literature-based values of root inputs and dissolved organic carbon exports. Peat CH4 fluxes (kg CH4 ha-1 yr-1) were insignificant in oil palm (0.3 ± 0.4) while emissions in forest were high (14.0 ± 2.8), and larger in wet than in dry months. N2O emissions (kg N2O ha-1 yr-1) were highly variable spatially and temporally and similar across land-uses (5.0 ± 3.9 and 5.2 ± 3.7 in oil palm and forest). Temporal variation of CH4 was controlled by water table level and soil water-filled pore space in forest and oil palm, respectively. Monthly fluctuations of N2O were linked to water table level in forest. The peat GHG budget (expressed in emissions Mg CO2e ha-1 yr-1) in oil palm (31.7 ± 8.6) was nearly eight times the budget in forest (4.0 ± 4.8). It was also ten times higher in one of the forests which was secondary (10.2 ± 4.5) than in the primary forests (0.9 ± 3.9). In oil palm 96% of emissions were released as CO2 whereas in forest CH4 and N2O together contributed 65% to the budget. Our study highlights the disastrous atmospheric impact associated with land-use change in tropical peatlands, with and without drainage.